FIFTEEN YEARS OF JURNAL SYARIAH (1993-2007): A BIBLIOMETRIC STUDY - Abdullah, Raihanah; Ab Rahman, Asmak (Malaysian Journal of Library and Information Science, 2009)
This study presents the result of various bibliometric patterns of articles published by the Jurnal Syariah for the period of 1993-2007. This Malaysian academic journal is devoted to the field of classical Islamic Law and its applications in modern times today. Data from each selected issue of the Jurnal Syariah were collected and statistically analysed using the Statistical Product and Service Solutions (SPSS). The study looked at variables which include authorship patterns, length of articles, number of articles published, author productivity, contributing institutions and subject area patterns. Among the significant findings are that single authorship is prevalent and accounted for about 90% of the articles published and the total number of articles published fo th period of 1993-2007 was 285 articles. It was found that 89% of the articles were published in the Malay language. As for the references used, 98% were books, and 39% were journals cited This study has demonstrated that despite its fifteen years of existenc and multidisciplinar approach, contributors and citations of this journal has not yet international. Henceforth, this article provides significant suggestions and strategies for the future of the Jurnal Syariah.